JURIDICAL ANALYSIS OF BANKING INSTITUTIONS’ LIABILITY FOR CARDING CRIMES - Novitasari, Arina; Putra, Dika Anggara; Rosita, Dian (Yayasan Amanah Nur Aman, 2025)
The rapid development of technology has brought humanity into a wave of modernization characterized by digitalization, leading to significant changes in all aspects of human life. The role of technology today offers various conveniences. The transformation of payment systems from cash-based to cashless transactions provides ease for customers and helps reduce the risk of crimes such as robbery, theft, and counterfeiting. One of the most widely used cashless payment methods that is frequently misused by irresponsible individuals for criminal purposes today is the credit card. The focus of this study is to examine the legal accountability of banking institutions in relation to a specific type of cybercrime, namely carding, which causes financial losses to customers. This research employs a normative juridical method. The findings indicate that the bank’s liability from a civil law perspective refers to Article 1338 paragraph (1) of the Indonesian Civil Code and Article 19 paragraph (1) of Law No. 8 of 1999 concerning Consumer Protection. Customer losses resulting from carding crimes are viewed as a consequence of inadequate protection by the issuing bank in maintaining network security. Errors or negligence by bank employees can be construed as the bank’s responsibility; however, if it can be proven that the carding crime did not occur due to the issuing bank’s negligence, then the bank is not obliged to compensate for the losses suffered by the customer.